Circadian patterns of peak expiratory flow in healthy male individuals from different age groups - Shinde, Bhagvat V.; Irani, Farahanaz B.; Joshi, Prema (International Journal of Research in Medical Sciences, 2025)
Background: The human respiratory system exhibits circadian variation, with peak expiratory flow rate (PEFR) typically lowest in the early morning and highest in the evening. This study aimed to assess diurnal variations in PEFR across different age groups and evaluate the influence of aging on this physiological rhythm. Methods: A cross-sectional study was conducted on 145 healthy male volunteers aged 18–50 years, divided into two groups: 18-30 years (n=78) and 31-50 years (n=67). PEFR was recorded at four time points (7:00 AM, 12:00 PM, 7:00 PM, and 10:00 PM) over two days using mini-Wright’s peak flow meters. Data were analyzed using unpaired t-test, ANOVA, and Tukey’s post hoc test. Results: Both groups exhibited significant diurnal variation in PEFR (p<0.0001), with morning troughs and evening peaks. The younger group consistently showed higher PEFR values at all-time points (p<0.0001) and a greater amplitude of variation. The largest increase occurred between 7 AM and 7 PM. No significant differences were observed between 12 pm and 10 pm in either group, indicating a plateau after the evening peak. BMI was comparable between groups, ruling it out as a confounder. Conclusions: PEFR demonstrates a clear circadian pattern in healthy adult males, with aging associated with reduced values and diminished amplitude of variation. These findings underscore the importance of considering time-of-day and age in pulmonary function assessment. Clinically, they support time-based monitoring and interventions, particularly in conditions like asthma, where diurnal variation is exaggerated.